The Role Of Health Education Through Social Media In Detecting NCDs Among Adolescents - Raule, Jean Henry (Oshada, 2025)
Non-communicable diseases (NCDs) such as obesity, hypertension, and diabetes are increasingly becoming serious challenges to the health of adolescents in Indonesia, primarily due to modern lifestyles heavy on fast food consumption, low physical activity, and exposure to tobacco and alcohol. Recent data shows that the prevalence of overweight and obesity among Indonesian adolescents is at an alarming rate, yet awareness of early detection remains low, resulting in many cases going undiagnosed until they reach their productive years. Adolescence is a critical period in the formation of lifestyles that will have long-term impacts on health, so early educational interventions are crucial to instilling healthy lifestyles. In this context, social media is a strategic tool because it is closely related to the lives of millennials and Gen Z, who are active in the digital space. Platforms like Instagram, TikTok, and YouTube have proven effective in conveying health messages in a visual, interactive, and accessible manner. Integrating digital education strategies with health promotion theories such as the Health Belief Model and national policies through the Germas (Healthy Living Movement) and CERDIK campaigns allows for more contextual and applicable messages. Furthermore, the involvement of influencers and healthcare professionals increases the credibility of content and encourages changes in healthy behavior. With a cross-sectoral approach involving families, schools, communities, and government, social media can transform into a sustainable health education ecosystem. This effort is expected to reduce the prevalence of NCDs, improve adolescent health literacy, and develop a healthy, productive, and competitive young generation